2011
DOI: 10.1007/s12157-011-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

Couverture vaccinale contre l’hépatite virale B et prévalence de l’antigène HBs dans une profession à risque: étude transversale portant sur 244 sapeurs-pompiers de la ville d’Abidjan

Abstract: But : Déterminer la couverture vaccinale contre l'hépatite virale B et la prévalence de l'antigène HBs chez les sapeurs-pompiers. Matériels et méthodes : Il s'agissait d'une étude transversale réalisée lors d'une journée publique de dépistage volontaire et gratuit de l'antigène HBs. Tous les sapeurs-pompiers militaires qui se sont présentés ont été soumis à un questionnaire sous forme d'interview (âge, sexe, vaccination contre l'hépatite virale B), suivi d'une recherche de l'antigène HBs et du dosage des trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
4
1
4
Order By: Relevance
“…Anti-HBs titration was performed by using a sandwich ELISA technique (MONOLISA Anti-HBs PLUS, Bio-Rad, Marnes-la-Coquette, France). HBsAg and total anti-HBc antibodies were detected by elec- coverage was higher in this laboratory than those reported at a national level which was estimated to 24.7 [3]. It was also higher than those of studies conducted in South African [11] and Pakistan [12] studies, which reported vaccine coverage against HBV of 72.5% and 73.4%, respectively among the health staff surveyed.…”
Section: Methodscontrasting
confidence: 68%
See 2 more Smart Citations
“…Anti-HBs titration was performed by using a sandwich ELISA technique (MONOLISA Anti-HBs PLUS, Bio-Rad, Marnes-la-Coquette, France). HBsAg and total anti-HBc antibodies were detected by elec- coverage was higher in this laboratory than those reported at a national level which was estimated to 24.7 [3]. It was also higher than those of studies conducted in South African [11] and Pakistan [12] studies, which reported vaccine coverage against HBV of 72.5% and 73.4%, respectively among the health staff surveyed.…”
Section: Methodscontrasting
confidence: 68%
“…In Ivory Coast however, only children under 11 months are eligible for free vaccination through the Expanded Program on Immunization (EPI) implemented in the country [9]. Therefore, anti-HBV vaccination is not free of charge, neither mandatory for HCWs for which it should systematically be done [3]. Also, for people vaccinated against HBV, but at high risk for infection, there is a need to check for the effectiveness of immunization by titration of antibodies against Hepatitis B surface antigen (anti-HBs) [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Du fait de leur coût astronomique 11 ils sont inaccessibles, sauf pour les patients 4 Ces sérologies sont financées par le PEPFAR, acronyme de « President's Emergency Plan for Aids Relief » désignant le programme de lutte contre le VIH/sida du Président des États-Unis George W. Bush. 5 La recherche de l'AgHBs ou des Ac anti-VHC coûte au minimum 4 000 Fcfa, soit environ 6 €.…”
Section: Des Traitements Inabordablesunclassified
“…En Côte d'Ivoire, en particulier, le VIH/sida est une pré-occupation de santé publique depuis les années 1990 [3] et les traitements antirétroviraux gratuits depuis 2008. Les hépatites virales ne bénéficient pas du même engagement, alors que la prévalence du VHB y serait de plus de 10% [4][5][6][7][8][9][10][11]. Pour assurer la sécurité transfusionnelle, le Centre National de Transfusion Sanguine (CNTS) pratique le dépis-tage systématique du VIH depuis 1992, la recherche de l'antigène HBs (AgHBs) depuis 1993 et celle des anticorps anti-VHC (Ac anti-VHC) depuis 1997.…”
Section: Introductionunclassified